Deskripsi Kemampuan Membaca Permulaan Menggunakan Adaptasi Early Grade Reading Asesment (EGRA) Peserta Didik Kelas 1 - Novita Sari, Theresia; Halidjah, Siti; Vilda Ghasya, Dyoty Auliya (Innovative: Journal Of Social Science Research, 2024)
This study aims to describe the initial reading ability using the Early Grade Reading Assessment (EGRA) adaptation in class 1B students of Elementary School 18 Pontianak Utara. The method used in this study is a quantitative descriptive method using the Early Grade Reading Assessment (EGRA) test adaptation. The source of this study was 28 students of class 1B Elementary School 18 Pontianak Utara. The instrument in this study used an instrument in the form of an EGRA test consisting of 5 questions. The results of the study showed that the initial reading ability of students using the Early Grade Reading Assessment (EGRA) test, namely in the aspect of recognizing letters, 82% of students already recognized letters well and 17% of students were still lacking in recognizing letters. In the aspect of reading meaningful words, 57% of students were able to read meaningful words well and 50% of students were not yet able to read meaningful words. In the aspect of reading meaningless words, 65.5% of students were not yet able to read meaningless words and 41% were able to read meaningless words quite well. In terms of reading aloud fluency (comprehension), 53.5% of students were able to read aloud well and 46% of students were not yet able to read aloud. In terms of listening (comprehension/listening), 71% of students were able to listen well and 28.5% of students were still lacking in listening. The difficulties of students in beginning reading: only recognizing a few letters, reversing letters, changing words, spelling hesitantly, lack of focus in listening to the reading.